Are Mutual Fund Managers Paid for Investment Skill? - Ibert, Markus; Kaniel, Ron; Nieuwerburgh, Stijn Van; Vestman, Roine (Review of Financial Studies, 2018)
Compensation of mutual fund managers is paramount to understanding agency frictions in asset delegation. We collect a unique registry-based dataset on the compensation of Swedish mutual fund managers. We find a concave relationship between pay and revenue, in contrast to how investors compensate the fund company (firm). We also find a surprisingly weak sensitivity of pay to performance, even after accounting for the indirect effects of performance on revenue. Firm-level fixed effects, revenues, and profits add substantial explanatory power for compensation.